An integrated framework using high‐dimensional mass cytometry and fluorescent flow cytometry identifies discrete B cell subsets in patients with red meat allergy. Issue 5 (8th January 2019) - Cox, Kelly M.; Commins, Scott P.; Capaldo, Brian J.; Workman, Lisa J.; Platts‐Mills, Thomas A. E.; Amir, El‐ad D.; Lannigan, Josephine A.; Schuyler, Alexander J.; Erickson, Loren D.
Summary: Background: B cells play a critical role in the development and maintenance of food allergy by producing allergen‐specific IgE. Despite the importance of B cells in IgE‐mediated food allergy, the identity of sIgE‐producing human B cells and how IgE is regulated are poorly understood. Objective: To identify the immunophenotypes of circulating B cells associated with the production of galactose‐alpha‐1, 3‐galactose‐specific IgE production in patients with red meat allergy. Methods: B cells in PBMC samples obtained from 19 adults with physician‐diagnosed red meat allergy and 20 non‐meat allergic healthy controls were assessed by mass cytometry along with a bioinformatics analysis pipeline to identify discrete B cell phenotypes that associated with serum sIgE. Fluorescent flow cytometry was then applied to sort purify discrete B cell subsets, and B cells were functionally evaluated on an individual cell level for the production of sIgE by ELISPOT. Results: Discrete B cell phenotypes abundant in meat allergic subjects compared to non‐meat allergic controls were found in peripheral blood that do not share typical characteristics of classical isotype‐switched memory B cells that express high levels of CD27. These B cell subsets shared higher IgD and lower IgM expression levels coupled with CXCR4, CCR6 and CD25 expression. In vitro polyclonal stimulation of purified B cell subsets from meat allergic subjects demonstrated that these subsets were enriched for cells induced to secrete sIgE. Conclusions and Clinical Relevance: Circulating B cells display increased abundance of discrete B cell subsets in meat allergic subjects. This observation, coupled with the capacity of individual B cell subsets to produce sIgE following activation, implicates these novel B cell phenotypes in promoting IgE in meat allergy.